Legal Analysis of Joint and Continuing Corruption Crimes in the Misuse of Specialized Personal Medical Devices: A Case Study of Pekanbaru District Court Decision No. 59/Pid.sus.TPK/2018/PN.Pbr - Ul Ikhwan, Amri; Sidi, Redyanto; Rahman Maulana, Abdul (PT. Multidisciplinary Press Indonesia, 2025)
This study analyzes the legal regulation and accountability concerning joint and continuing corruption offenses involving the misuse of specialized personal medical devices at the Regional Public Hospital (RSUD) Arifin Achmad, based on Pekanbaru District Court Decision No. 59/Pid.sus.TPK/2018/PN.Pbr. Corruption cases in healthcare remain prevalent, particularly involving medical device procurement and utilization. This research employs a normative juridical method by examining legal principles, statutes, and court rulings related to corruption in healthcare. Findings indicate that the corruption charges related to the misuse of specialized personal medical devices may more appropriately fall within civil law rather than criminal law. Furthermore, the hospital institution and its director should bear legal responsibility alongside the defendant and associated parties. The study highlights the importance of rigorous application of regulations concerning state financial losses and stresses that not all cases should be adjudicated as pure criminal acts, adhering to the principle of ultimum remedium. Recommendations include a thorough review and application of relevant legal regulations to ensure fair protection for defendants and uphold justice for the state. This study contributes to strengthening legal certainty and protection in the healthcare sector, particularly against corruption.